2004
DOI: 10.1083/jcb.200309101
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic redistribution of raft domains as an organizing platform for signaling during cell chemotaxis

Abstract: Spatially restricted activation of signaling molecules governs critical aspects of cell migration; the mechanism by which this is achieved nonetheless remains unknown. Using time-lapse confocal microscopy, we analyzed dynamic redistribution of lipid rafts in chemoattractant-stimulated leukocytes expressing glycosyl phosphatidylinositol–anchored green fluorescent protein (GFP-GPI). Chemoattractants induced persistent GFP-GPI redistribution to the leading edge raft (L raft) and uropod rafts of Jurkat, HL60, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
200
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(213 citation statements)
references
References 44 publications
11
200
2
Order By: Relevance
“…Alternatively, as exogenous mutant receptors are expressed at a higher level than endogenous receptors, CD44 S291A and S316A mutants may disrupt downstream signalling events by displacing endogenous CD44 from plasma membrane microdomains. One demonstrated function of such domains is to organize the gradient-sensing machinery to the leading edge of migrating cells (Gomez-Mouton et al, 2004). It is certainly of interest that in migratory cells, including NIH-3T3 cells, a proportion of CD44 is partitioned into detergent-insoluble glycolipid enriched microdomains whereas in non-migratory cells, all of the CD44 population can be extracted into a detergent-soluble fraction (Neame et al, 1995;Perschl et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, as exogenous mutant receptors are expressed at a higher level than endogenous receptors, CD44 S291A and S316A mutants may disrupt downstream signalling events by displacing endogenous CD44 from plasma membrane microdomains. One demonstrated function of such domains is to organize the gradient-sensing machinery to the leading edge of migrating cells (Gomez-Mouton et al, 2004). It is certainly of interest that in migratory cells, including NIH-3T3 cells, a proportion of CD44 is partitioned into detergent-insoluble glycolipid enriched microdomains whereas in non-migratory cells, all of the CD44 population can be extracted into a detergent-soluble fraction (Neame et al, 1995;Perschl et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 is a seven-transmembrane-domain receptor coupled to heterotrimeric proteins of the G i family and its engagement by CXCL12 evokes activation of a multiplicity of signalling pathways: among these, activation of phosphoinositide 3-kinase and/or extracellular signal-regulated kinases have been shown to provide key events for chemotaxis induction in a variety of cell systems [3,5,[8][9][10]. Notably, evidence has been provided that signalling through CXCR4 may be sensitive to the receptor lipid environment.…”
Section: Introductionmentioning
confidence: 99%
“…With several receptor classes, incorporation of the receptors into lipid rafts increases signaling efficiency, 34,50,51 and thus, if CXCR4 would be incorporated into rafts during priming with C3a, then it might be able to signal with lower concentrations of SDF-1. Accordingly, the hypothesis that the priming effect of C3a and C3a des-Arg was dependent on membrane lipid raft formation was investigated.…”
Section: C3a and C3a Des-arg Increase The Incorporation Of Cxcr4 Intomentioning
confidence: 99%
“…[30][31][32][33] Lipid rafts have been shown to be important for T-cell polarization and chemotaxis. 30,34 To learn more about the role of C3 in HSC engraftment, this study employed C3 À/À mice and their WT littermates as a model. Since it was observed that these mice had a defect in hematopoietic recovery after transplantation, it was of interest to determine if the C3 cleavage fragments C3a, C3a des-Arg and iC3b modulated the engraftment and homing of HSPC in BM.…”
Section: Introductionmentioning
confidence: 99%